Current Practice in Diagnosis and Treatment of Growth Hormone Deficiency in Childhood: A Survey from Turkey - Poyrazoglu, Sukran; Akcay, Teoman; Arslanoglu, Ilknur; Atabek, Mehmet Ernie; Atay, Zeynep; Berberoglu, Merih; Darendeliler, Feyza (Galenos Yayincilik, 2015)
Objective: Approaches to diagnosis and treatment of growth hormone deficiency (GHD) in children vary among countries and even among centers in the same country. This survey, aiming to facilitate the process of preparing the new consensus on GHD by the Turkish Pediatric Endocrinology and Diabetes Society, was designed to evaluate the current practices in diagnosis and treatment of GHD in different centers in Turkey. Methods: A questionnaire covering relevant items for diagnosis and treatment of GHD was sent out to all pediatric endocrinology centers. Results: Twenty-four centers returned the questionnaire. The most frequently used GH stimulation test was L-dopa, followed by clonidine. Eighteen centers used a GH cut-off value of 10 ng/mL for the diagnosis of GHD; this value was 7 ng/mL in 4 centers and 5 ng/mL in 2 centers. The most frequently used assay was immunochemiluminescence for determination of GH, insulin-like growth factor-1 and insulin-like growth factor binding protein-3 concentrations. Sex steroid priming in both sexes was used by 19 centers. The most frequently used starting dose of recombinant human GH (rhGH) in prepubertal children was 0.025-0.030 mg/kg/day and 0.030-0.035 mg/kg/day in pubertal children. Growth velocity was used in the evaluation for growth response to rhGH therapy in all centers. Anthropometric measurements of patients every 3-6 months, fasting blood glucose, bone age and thyroid panel evaluation were used by all centers at follow-up. Main indications for cessation of therapy were decreased height velocity and advanced bone age. Fourteen centers used combined treatment (rhGH and gonadotropin-releasing analogues) to increase final height. Conclusion: Although conformity was found among centers in Turkey in current practice, it is very important to update guideline statements and to modify, if needed, the approach to GHD over time in accordance with new evidence-based clinical studies.
Keywords: Survey; growth hormone deficiency; childhood